Development of upper-extremity morphological asymmetries in male and female elite youth tennis players: A longitudinal study - Chapelle, L.; D`Hondt, E.; Rommers, N.; Clarys, P. (Pediatric Exercise Science, 2024)
Purpose This 2-year longitudinal study examined the development of upper-extremity bone mineral density (BMD), bone mineral content (BMC), and lean mass (LM) asymmetry magnitudes in male and female youth tennis players.